2003
DOI: 10.1007/bf03027225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precipitate and dendrite arm spacing on tensile properties and fracture behavior of As-Cast magnesium-aluminum alloys

Abstract: In the present study, the fracture behavior of Mg 17 Al 12 precipitate and the effect of dendrite arm spacing (DAS) on tensile properties of commercial as-cast AZ91D alloy were discussed. In order to obtain a wide range of DAS, the as-cast specimens were fabricated by various casting processes. With gravity-casting, the inoculation and various molds were utilized, and the solidification rates of melts were measured at four positions of the cone-type mold. The empirical equation between the solidification rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…The use of microalloying addition for this purpose has attracted considerable attention for age hardening Mg-Sn based alloys [13]. However, the continuous network of Mg 17 Al 12 phases along the grain boundaries leads to intergranular fracture, such as AZ91D alloy [14]. The strength decreased with increasing test temperature, as expected.…”
Section: Microstructuresmentioning
confidence: 64%
“…The use of microalloying addition for this purpose has attracted considerable attention for age hardening Mg-Sn based alloys [13]. However, the continuous network of Mg 17 Al 12 phases along the grain boundaries leads to intergranular fracture, such as AZ91D alloy [14]. The strength decreased with increasing test temperature, as expected.…”
Section: Microstructuresmentioning
confidence: 64%
“…[ 34 ] The solute segregation‐induced strengthening by interaction with dislocations has been revealed in models. [ 82,83 ] Some researchers proposed that the yield strength abides by a Hall–Petch relationship with the DAS for cast alloys; [ 84,85 ] however, Hall–Petch relationship between yield strength and mean grain size, d , (σnormaly=σfr+kd1/2, where k is the strengthening coefficient) has been more widely used in HEAs. [ 11,34,86 ] The grains of these HEAs in as‐cast state are very coarse with the average sizes >500 μm from the SEM images; the exact values of which were difficult to determine as the dendrites are stereoscopic in space.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study by Sharifi et al [41] showed an increase in flow stress in samples with a refined cast grain structure in AM60 and AZ91 at low levels of plastic strain. The tensile properties affected by dendrite arm spacing have also been thoroughly studied for magnesium-aluminum alloys and follow the Hall-Petch relationship with respect to increasing yield strength with decreasing grain size [42]. When comparing the effects of solidification rate and ageing on mechanical properties of AZ91, Cáceres et al [26] found no definitive correlation between solidification rate (and consequently the SDAS) and the room temperature yield strength or ductility of the material, though this is attributed to the dissolving of the γ-Mg 17 Al 12 particles, effectively erasing the dendritic structure.…”
Section: Effect Of Initial State On Deformation Behaviourmentioning
confidence: 99%